Analisa Proses Repair dan Pengukuran Vibrasi Motor Listrik Compressor 250 Kw di PT. XYZ - Muhammad Riziq Mustofa; Rizal Hanifi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The use of induction motors without proper maintenance, or the use of motors that have been used for a long time will quickly be damaged, such as overheating (overhaul), overloading the power output, burning the motor, etc. All damage can be experienced by induction motors. Therefore, one way that can be done is by repairing (repair). Assessing an induction motor that has been repaired is to analyze the vibration of the induction motor, which must have a value according to ISO standards. In this study using a 250 kW induction motor as the object of research, the repair analysis starts from the initial inspection for physical damage, electricity, and measurements according to standards. Followed by the induction motor repairing process, then re-measurement to assess the repair according to applicable standards and analysis of vibration velocity and acceleration is carried out to determine the final result. The results of repairing a 250 kW electric motor on the bearings have undergone changes and repairs by adjusting the EASA tolerance hole, the shaft requires balancing treatment, and the vibration results measure in the horizontal (H), vertical (V), and axial (A) directions of the induction motor with Hinlet Veleocity RMS value 0.293 outlet